A glass fiber cloth and a method for manufacturing the same

CN118125728BActive Publication Date: 2026-10-23HAINING JIETE FIBERGLASS FABRIC CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410087018.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-22
Publication Date
2026-10-23
Estimated Expiration
2044-01-22

AI Technical Summary

Technical Problem

[0003]玻璃纤维本身吸水能力并不强,但由于玻璃纤维具有较高的比表面积,其吸附水的能力较强,当玻璃纤维吸附水后,会降低其电绝缘性能,导致纤维和树脂的结合能力降低,而影响强度;且吸附水后容易溶解玻璃纤维内的碱金属氧化物降低纤维强度

Benefits of technology

[0027]1、本发明在浸润剂中添加了纳米二氧化硅,浸润剂中环氧树脂以及酚醛树脂在玻璃纤维表面成膜,通过纳米二氧化硅的加入,填充树脂成膜时产生的间隙,降低玻璃纤维的比表面积,增强了玻璃纤维布的防水性能;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the field of glass fiber cloth manufacturing, in particular to glass fiber cloth and a preparation method thereof, which comprises the following steps: S1, polyacrylonitrile solution is coated on the surface of glass fiber, and the polyacrylonitrile-glass fiber is obtained after drying; S2, the polyacrylonitrile-glass fiber is carbonized to obtain carbon-based nanofiber-glass fiber; S3, the carbon-based nanofiber-glass fiber is etched in an etching solution to obtain reinforced glass fiber; S4, the reinforced glass fiber is twisted to obtain yarn, and the yarn is woven to obtain base glass fiber cloth; S5, the base glass fiber cloth is immersed in an impregnating agent for 2-3 hours, the excess impregnating agent on the base glass fiber cloth is squeezed, air bubbles are discharged, and the glass fiber cloth is obtained. The glass fiber cloth prepared by the preparation method has the characteristics of high mechanical strength and high water repellency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass fiber cloth manufacturing, and particularly to a glass fiber cloth and its preparation method. Background Technology

[0002] Glass fiber, as a high-performance inorganic non-metallic material, is often used as a reinforcing material in composite materials and is widely used. However, it is still a glass product and has the well-known disadvantages of being brittle and having poor wear resistance. In addition, glass fiber also has the following disadvantages.

[0003] Glass fiber itself does not have a strong water absorption capacity, but due to its high specific surface area, it has a strong ability to absorb water. When glass fiber absorbs water, it will reduce its electrical insulation properties, which will reduce the bonding ability between the fiber and the resin and affect the strength. In addition, after absorbing water, it is easy to dissolve the alkali metal oxides in the glass fiber, which will reduce the fiber strength.

[0004] After glass fiber is prepared, it usually needs to be coated with a sizing agent. However, the resin material in the sizing agent has a weak bonding ability with the fiber, and the incompatibility leads to a reduction in the mechanical properties of the glass fiber. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of weak waterproofing and mechanical properties of glass fiber as described in the background art. Here, a new glass fiber cloth and its preparation method are proposed. The glass fiber cloth prepared by this method has better waterproofing and stronger mechanical properties.

[0006] The technical solution adopted by this invention to solve its technical problem is: a method for preparing glass fiber cloth, which includes the following steps:

[0007] S1. A polyacrylonitrile solution is coated onto the surface of glass fiber, and then dried to obtain polyacrylonitrile-glass fiber.

[0008] S2. Carbonize the polyacrylonitrile-glass fiber to obtain carbon-based nanofibers-glass fiber;

[0009] S3. The carbon-based nanofibers-glass fibers are placed in an etching solution and etched to obtain reinforced glass fibers;

[0010] S4. The reinforcing glass fiber is twisted to obtain yarn, and the yarn is woven to obtain basic glass fiber cloth;

[0011] S5. After immersing the base fiberglass cloth in the sizing agent for 2-3 hours, remove it, squeeze out the excess sizing agent on the base fiberglass cloth, and remove the air bubbles to obtain the fiberglass cloth.

[0012] The mass concentration of the polyacrylonitrile solution is 5-15%, and the molecular weight of the polyacrylonitrile is 30,000-100,000.

[0013] The wetting agent comprises, by weight parts: 2-4 parts epoxy resin emulsion, 2-4 parts phenolic resin emulsion, 0.5-2 parts silane coupling agent, 2-4 parts polyethylene glycol, 2-6 parts nano silica, and 100 parts water.

[0014] In the above technical solution, a polyacrylonitrile solution is coated on the surface of glass fiber. By drying the solvent, the polyacrylonitrile solidifies on the surface of the glass fiber to form a polyacrylonitrile nanofiber film. Then, the polyacrylonitrile nanofiber film is carbonized by heating to form a carbon-based nanofiber film. This carbon-based nanofiber film can enhance the mechanical properties of the glass fiber. The surface of the carbon-based nanofiber film is etched by an etching solution to create "pits" on its surface and carry oxidative active groups on the fiber film. These active groups can react with the resin monomers in the sizing agent to greatly enhance the binding of the sizing agent to the glass fiber.

[0015] Preferably, the polyacrylonitrile solution in step S1 is prepared by dissolving polyacrylonitrile in dimethylformamide, heating to 55-65°C and stirring continuously for 6-12 hours.

[0016] Preferably, the mass concentration of polyacrylonitrile in the polyacrylonitrile solution in step S1 is 8-12%, and the molecular weight of the polyacrylonitrile is 50,000-100,000.

[0017] In the above technical solution, the mass concentration and molecular weight of polyacrylonitrile affect the adhesion and formation of polyacrylonitrile fiber film on the glass fiber surface. When the mass concentration is low, it is difficult to form a complete fiber film, while a high mass concentration leads to the accumulation of fiber film and uneven glass fiber. A low molecular weight also makes it difficult to form a fiber film.

[0018] Preferably, the specific steps of carbonization in step S2 are as follows: the polyacrylonitrile-glass fiber is placed in a carbonization furnace, heated to 100-200℃ and kept at that temperature for 1-2 hours, and then heated to 300-500℃ for 1-2 hours under a nitrogen atmosphere.

[0019] Preferably, the etching solution in step S3 is selected from one or more of nitric acid, sulfuric acid, sodium chlorate solution, and sodium hypochlorite solution.

[0020] Preferably, the etching solution is a mixture of 65% nitric acid and 10% sodium chlorate solution in a mass ratio of 1:(1-5).

[0021] In the above technical solution, the etching solution plays a role in etching carbon-based nanofibers and adding oxidative active groups to the surface of carbon-based nanofibers.

[0022] Preferably, the polyethylene glycol is selected from PEG2000 or PEG4000.

[0023] Preferably, the silane coupling agent in the wetting agent is selected from one or more of γ-(methacryloyloxy)propyltrimethoxysilane, 3-aminopropyltriethoxysilane, vinyltrichlorosilane, and vinylmethyldimethoxysilane.

[0024] Preferably, the silane coupling agent is a mixture of 3-aminopropyltriethoxysilane, vinylmethyldimethoxysilane and vinyltrichlorosilane in a mass ratio of 1:(1-2):(1-2).

[0025] A glass fiber cloth prepared by the method described above has excellent waterproof performance and mechanical strength.

[0026] The beneficial effects of this invention are:

[0027] 1. The present invention adds nano-silica to the impregnating agent. The epoxy resin and phenolic resin in the impregnating agent form a film on the surface of the glass fiber. By adding nano-silica, the gaps generated during the resin film formation are filled, the specific surface area of ​​the glass fiber is reduced, and the waterproof performance of the glass fiber cloth is enhanced.

[0028] 2. The present invention coats a carbon-based nanofiber film on the surface of glass fiber. The carbon-based nanofiber film not only enhances the mechanical properties of the glass fiber, but also, because the surface of the film carries active groups after etching, the resin in the sizing agent can fill the gaps and react with the carbon-based fiber to enhance the bonding ability of the sizing agent on the surface of the glass fiber.

[0029] 3. The present invention uses a specific combination of silane coupling agents to firmly bond the glass fiber to the resin, thereby enhancing the mechanical properties of the glass fiber cloth. Detailed Implementation

[0030] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0031] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments according to this application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0032] The present invention will now be further illustrated with specific examples. The following embodiments are only for explaining the present invention and do not constitute a limitation thereof. The test samples and test procedures used in the following embodiments include the following (if the specific experimental conditions are not specified in the embodiments, they are usually performed according to conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following embodiments can be obtained commercially unless otherwise specified).

[0033] Example 1

[0034] A method for preparing glass fiber cloth, the specific steps of which are as follows:

[0035] S1. The glass fiber surface is coated with a polyacrylonitrile solution, and after coating, it is dried to obtain polyacrylonitrile-glass fiber. The polyacrylonitrile solution is prepared by dissolving polyacrylonitrile in dimethylformamide, heating to 60°C and stirring continuously for 10 hours. The mass concentration of the polyacrylonitrile solution is 10%, and the molecular weight of the polyacrylonitrile is 50,000.

[0036] S2. Carbonize the polyacrylonitrile-glass fiber prepared in step S1 to obtain carbon-based nanofibers-glass fiber. The specific steps of carbonization are as follows: place the polyacrylonitrile-glass fiber in a carbonization furnace, first heat it to 150°C and keep it at that temperature for 2 hours, and then heat it to 450°C for 2 hours under a nitrogen atmosphere.

[0037] S3. The carbon-based nanofibers-glass fibers obtained in step S2 are placed in an etching solution to etch and obtain reinforced glass fibers. The etching solution is prepared by mixing 65% nitric acid and 10% sodium chlorate solution in a mass ratio of 1:3.

[0038] S4. The reinforcing glass fiber obtained in step S3 is twisted to obtain yarn, and the yarn is woven into basic glass fiber cloth.

[0039] S5. After immersing the basic fiberglass cloth obtained in step S4 in the sizing agent for 2 hours, take it out, squeeze out the excess sizing agent on the basic fiberglass cloth, remove the air bubbles, and obtain the fiberglass cloth.

[0040] The wetting agent comprises, by mass parts: 4 parts epoxy resin emulsion, 2 parts phenolic resin emulsion, 2 parts silane coupling agent, 4 parts polyethylene glycol, 6 parts nano silica, and 100 parts water. The silane coupling agent is prepared by mixing 3-aminopropyltriethoxysilane, vinylmethyldimethoxysilane, and vinyltrichlorosilane in a mass ratio of 1:1:1.

[0041] Example 2

[0042] A method for preparing glass fiber cloth, the specific steps of which are as follows:

[0043] S1. The glass fiber surface is coated with a polyacrylonitrile solution, and after coating, it is dried to obtain polyacrylonitrile-glass fiber. The polyacrylonitrile solution is prepared by dissolving polyacrylonitrile in dimethylformamide, heating to 60°C and stirring continuously for 10 hours. The mass concentration of the polyacrylonitrile solution is 10%, and the molecular weight of the polyacrylonitrile is 50,000.

[0044] S2. Carbonize the polyacrylonitrile-glass fiber prepared in step S1 to obtain carbon-based nanofibers-glass fiber. The specific steps of carbonization are as follows: place the polyacrylonitrile-glass fiber in a carbonization furnace, first heat it to 150°C and keep it at that temperature for 2 hours, and then heat it to 450°C for 2 hours under a nitrogen atmosphere.

[0045] S3. The carbon-based nanofibers-glass fibers obtained in step S2 are placed in an etching solution to etch and obtain reinforced glass fibers. The etching solution is prepared by mixing 65% nitric acid and 10% sodium chlorate solution in a mass ratio of 1:3.

[0046] S4. The reinforcing glass fiber obtained in step S3 is twisted to obtain yarn, and the yarn is woven into basic glass fiber cloth.

[0047] S5. After immersing the basic fiberglass cloth obtained in step S4 in the sizing agent for 2 hours, take it out, squeeze out the excess sizing agent on the basic fiberglass cloth, remove the air bubbles, and obtain the fiberglass cloth.

[0048] The wetting agent comprises, by mass parts: 2 parts epoxy resin emulsion, 4 parts phenolic resin emulsion, 0.5 parts silane coupling agent, 2 parts polyethylene glycol, 2 parts nano silica, and 100 parts water. The silane coupling agent is prepared by mixing 3-aminopropyltriethoxysilane, vinylmethyldimethoxysilane, and vinyltrichlorosilane in a mass ratio of 1:1:1.

[0049] Example 3

[0050] A method for preparing glass fiber cloth, the specific steps of which are as follows:

[0051] S1. The glass fiber surface is coated with a polyacrylonitrile solution, and after coating, it is dried to obtain polyacrylonitrile-glass fiber. The polyacrylonitrile solution is prepared by dissolving polyacrylonitrile in dimethylformamide, heating to 60°C and stirring continuously for 10 hours. The mass concentration of the polyacrylonitrile solution is 10%, and the molecular weight of the polyacrylonitrile is 50,000.

[0052] S2. Carbonize the polyacrylonitrile-glass fiber prepared in step S1 to obtain carbon-based nanofibers-glass fiber. The specific steps of carbonization are as follows: place the polyacrylonitrile-glass fiber in a carbonization furnace, first heat it to 100°C and keep it at that temperature for 1 hour, and then heat it to 300°C for 1 hour under a nitrogen atmosphere.

[0053] S3. The carbon-based nanofibers-glass fibers obtained in step S2 are placed in an etching solution to etch and obtain reinforced glass fibers. The etching solution is prepared by mixing 65% nitric acid and 10% sodium chlorate solution in a mass ratio of 1:5.

[0054] S4. The reinforcing glass fiber obtained in step S3 is twisted to obtain yarn, and the yarn is woven into basic glass fiber cloth.

[0055] S5. After immersing the basic fiberglass cloth obtained in step S4 in the sizing agent for 2 hours, take it out, squeeze out the excess sizing agent on the basic fiberglass cloth, remove the air bubbles, and obtain the fiberglass cloth.

[0056] The wetting agent comprises, by mass parts: 4 parts epoxy resin emulsion, 2 parts phenolic resin emulsion, 2 parts silane coupling agent, 4 parts polyethylene glycol, 6 parts nano silica, and 100 parts water. The silane coupling agent is prepared by mixing 3-aminopropyltriethoxysilane, vinylmethyldimethoxysilane, and vinyltrichlorosilane in a mass ratio of 1:1:1.

[0057] Example 4

[0058] A method for preparing glass fiber cloth, the specific steps of which are as follows:

[0059] S1. The glass fiber surface is coated with a polyacrylonitrile solution and dried after coating to obtain polyacrylonitrile-glass fiber. The polyacrylonitrile solution is prepared by dissolving polyacrylonitrile in dimethylformamide, heating to 65°C and stirring continuously for 12 hours. The mass concentration of the polyacrylonitrile solution is 15%, and the molecular weight of the polyacrylonitrile is 100,000.

[0060] S2. Carbonize the polyacrylonitrile-glass fiber prepared in step S1 to obtain carbon-based nanofibers-glass fiber. The specific steps of carbonization are as follows: place the polyacrylonitrile-glass fiber in a carbonization furnace, first heat it to 150°C and keep it at that temperature for 2 hours, and then heat it to 450°C for 2 hours under a nitrogen atmosphere.

[0061] S3. The carbon-based nanofibers-glass fibers obtained in step S2 are placed in an etching solution to etch and obtain reinforced glass fibers. The etching solution is prepared by mixing 65% nitric acid and 10% sodium chlorate solution in a mass ratio of 1:3.

[0062] S4. The reinforcing glass fiber obtained in step S3 is twisted to obtain yarn, and the yarn is woven into basic glass fiber cloth.

[0063] S5. After immersing the basic fiberglass cloth obtained in step S4 in the sizing agent for 2 hours, take it out, squeeze out the excess sizing agent on the basic fiberglass cloth, remove the air bubbles, and obtain the fiberglass cloth.

[0064] The wetting agent comprises, by mass parts: 4 parts epoxy resin emulsion, 2 parts phenolic resin emulsion, 2 parts silane coupling agent, 3 parts polyethylene glycol, 6 parts nano silica, and 100 parts water. The silane coupling agent is prepared by mixing 3-aminopropyltriethoxysilane, vinylmethyldimethoxysilane, and vinyltrichlorosilane in a mass ratio of 1:1:1.

[0065] Example 5

[0066] A method for preparing glass fiber cloth, the specific steps of which are as follows:

[0067] S1. The glass fiber surface is coated with a polyacrylonitrile solution and dried after coating to obtain polyacrylonitrile-glass fiber. The polyacrylonitrile solution is prepared by dissolving polyacrylonitrile in dimethylformamide, heating to 55°C and stirring continuously for 8 hours. The mass concentration of the polyacrylonitrile solution is 5%, and the molecular weight of the polyacrylonitrile is 30,000.

[0068] S2. Carbonize the polyacrylonitrile-glass fiber prepared in step S1 to obtain carbon-based nanofibers-glass fiber. The specific steps of carbonization are as follows: place the polyacrylonitrile-glass fiber in a carbonization furnace, first heat it to 150°C and keep it at that temperature for 2 hours, and then heat it to 450°C for 2 hours under a nitrogen atmosphere.

[0069] S3. The carbon-based nanofibers-glass fibers obtained in step S2 are placed in an etching solution to etch and obtain reinforced glass fibers. The etching solution is prepared by mixing 65% nitric acid and 10% sodium chlorate solution in a mass ratio of 1:3.

[0070] S4. The reinforcing glass fiber obtained in step S3 is twisted to obtain yarn, and the yarn is woven into basic glass fiber cloth.

[0071] S5. After immersing the basic fiberglass cloth obtained in step S4 in the sizing agent for 2 hours, take it out, squeeze out the excess sizing agent on the basic fiberglass cloth, remove the air bubbles, and obtain the fiberglass cloth.

[0072] The wetting agent comprises, by mass parts: 4 parts epoxy resin emulsion, 2 parts phenolic resin emulsion, 2 parts silane coupling agent, 3 parts polyethylene glycol, 6 parts nano silica, and 100 parts water. The silane coupling agent is prepared by mixing 3-aminopropyltriethoxysilane, vinylmethyldimethoxysilane, and vinyltrichlorosilane in a mass ratio of 1:1:1.

[0073] Example 6

[0074] A method for preparing glass fiber cloth, the specific steps of which are as follows:

[0075] S1. The glass fiber surface is coated with a polyacrylonitrile solution, and after coating, it is dried to obtain polyacrylonitrile-glass fiber. The polyacrylonitrile solution is prepared by dissolving polyacrylonitrile in dimethylformamide, heating to 60°C and stirring continuously for 10 hours. The mass concentration of the polyacrylonitrile solution is 10%, and the molecular weight of the polyacrylonitrile is 50,000.

[0076] S2. Carbonize the polyacrylonitrile-glass fiber prepared in step S1 to obtain carbon-based nanofibers-glass fiber. The specific steps of carbonization are as follows: place the polyacrylonitrile-glass fiber in a carbonization furnace, first heat it to 200°C and keep it at that temperature for 2 hours, and then heat it to 500°C for 2 hours under a nitrogen atmosphere.

[0077] S3. The carbon-based nanofibers-glass fibers obtained in step S2 are placed in an etching solution to etch and obtain reinforced glass fibers. The etching solution is prepared by mixing 65% nitric acid and 10% sodium chlorate solution in a mass ratio of 1:1.

[0078] S4. The reinforcing glass fiber obtained in step S3 is twisted to obtain yarn, and the yarn is woven into basic glass fiber cloth.

[0079] S5. After immersing the basic fiberglass cloth obtained in step S4 in the sizing agent for 3 hours, take it out, squeeze out the excess sizing agent on the basic fiberglass cloth, remove the air bubbles, and obtain the fiberglass cloth.

[0080] The wetting agent comprises, by mass parts: 4 parts epoxy resin emulsion, 2 parts phenolic resin emulsion, 2 parts silane coupling agent, 4 parts polyethylene glycol, 6 parts nano silica, and 100 parts water. The silane coupling agent is prepared by mixing 3-aminopropyltriethoxysilane, vinylmethyldimethoxysilane, and vinyltrichlorosilane in a mass ratio of 1:2:2.

[0081] Comparative Example 1 (without nano-silica)

[0082] A method for preparing glass fiber cloth, the steps of which are the same as those in Example 1, except that nano-silica is not added to the impregnating agent.

[0083] Comparative Example 2 (without carbon-based nanofiber-glass fiber etching treatment)

[0084] A method for preparing glass fiber cloth, the steps of which are similar to those in Example 1, except that step S3 is omitted.

[0085] Test case

[0086] The glass fiber cloths prepared in Examples 1-7 and Comparative Examples 1-2 were tested for bending degree, impact strength and water repellency, and the test results are shown in Table 1.

[0087] Among them, the bending degree test adopts the GB / T 8805-1988 test standard, the impact strength test adopts the GB 1697-82 test standard, and the water repellency test adopts the JIS L1092-2009 test standard.

[0088] Table 1. Test results of fiberglass cloth's bending degree, impact strength, and water repellency.

[0089] Example 1 565 569 98 Example 2 562 562 96 Example 3 562 560 95 Example 4 566 571 99 Example 5 560 556 95 Example 6 562 560 96 Comparative Example 1 565 568 92 Comparative Example 2 564 565 94

[0090] As can be seen from Table 1, the glass fiber cloths prepared in Examples 1-6 all have good bending and anti-filler strength, which shows that the glass fiber cloth prepared by the present invention has good mechanical strength. This is due to the bonding of carbon-based nanofibers to the surface of glass fiber, and the good bonding ability between carbon-based nanofibers and resin emulsion, which improves the mechanical strength of glass fiber cloth.

[0091] As can be seen from the comparison between Comparative Example 1 and Example 1, the addition of nano-silica improves the waterproof performance of the product, which is due to the fact that nano-silica fills the gaps between resin monomers.

[0092] As can be seen from the comparison between Example 1 and Example 6, the ratio of coupling agent has an impact on the mechanical properties of glass fiber. A suitable ratio of coupling agent can further enhance the bonding ability between resin and glass fiber, thereby changing the mechanical properties of glass fiber.

[0093] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on its differences from other embodiments. Similar or identical parts between embodiments can be referred to interchangeably. For the apparatus disclosed in the embodiments, since it corresponds to the method disclosed in the embodiments, the description is relatively simple; relevant parts can be referred to in the method section.

[0094] The present invention has provided a detailed description of a glass fiber cloth and its preparation method. Specific examples have been used to illustrate the principles and implementation methods of the invention. The descriptions of these examples are merely for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make various improvements and modifications to the present invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing glass fiber cloth, characterized in that: The preparation method includes the following steps: S1. A polyacrylonitrile solution is coated onto the surface of glass fiber, and then dried to obtain polyacrylonitrile-glass fiber. S2. Carbonize the polyacrylonitrile-glass fiber to obtain carbon-based nanofibers-glass fiber. The specific steps are as follows: place the polyacrylonitrile-glass fiber in a carbonization furnace, first heat it to 100-200℃ and keep it at that temperature for 1-2 hours, and then heat it to 300-500℃ for 1-2 hours under a nitrogen atmosphere. S3. The carbon-based nanofibers-glass fibers are etched in an etching solution to obtain reinforced glass fibers. The etching solution is a mixture of 65% nitric acid and 10% sodium chlorate solution in a mass ratio of 1:(1-5). S4. The reinforcing glass fiber is twisted to obtain yarn, and the yarn is woven to obtain basic glass fiber cloth; S5. After immersing the base fiberglass cloth in the sizing agent for 2-3 hours, remove it, squeeze out the excess sizing agent on the base fiberglass cloth, and remove the air bubbles to obtain the fiberglass cloth. The mass concentration of the polyacrylonitrile solution is 5-15%, and the molecular weight of the polyacrylonitrile is 30,000-100,000. The impregnating agent comprises, by mass parts: 2-4 parts epoxy resin emulsion, 2-4 parts phenolic resin emulsion, 0.5-2 parts silane coupling agent, 2-4 parts polyethylene glycol, 2-6 parts nano silica, and 100 parts water; the silane coupling agent is a mixture of 3-aminopropyltriethoxysilane, vinylmethyldimethoxysilane, and vinyltrichlorosilane in a mass ratio of 1:(1-2):(1-2).

2. The preparation method according to claim 1, characterized in that: The preparation method of the polyacrylonitrile solution in step S1 is as follows: dissolve polyacrylonitrile in dimethylformamide, heat to 55-65℃ and stir continuously for 6-12 hours.

3. The preparation method according to claim 1, characterized in that: In step S1, the mass concentration of polyacrylonitrile in the polyacrylonitrile solution is 8-12%, and the molecular weight of the polyacrylonitrile is 50,000-100,000.

4. The preparation method according to claim 1, characterized in that: The polyethylene glycol is selected from PEG2000 or PEG4000.

5. A glass fiber cloth prepared by any one of claims 1-4.

Citation Information

Patent Citations

  • In-situ synthesis of nanometer oxide, and applications of the nanometer oxide in polyester carbon fiber sizing agents and basalt fiber / glass fiber sizing agents

    CN110128034A

  • Glass fiber cloth and preparation method thereof

    CN115028361A

  • Composite active carbon fibre and preparation process thereof

    CN1792936A